2017
DOI: 10.3390/su9040636
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Risk Disclosure: An Exploratory Study on Sustainability Reports

Abstract: Recent policy changes in sustainability reporting, such as the ones related to the new European Directive on non-financial disclosure (2014/95/EU), the standards issued by the American Sustainability Accounting Standard Board (SASB), the G4 guidelines issued by the Global Sustainability Standard Board (GSSB), and the framework of the International Integrated Reporting Council (IIRC) stress the importance of extending the disclosure of ethical, social, and environmental risks within financial and social-environ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 81 publications
(73 reference statements)
1
63
0
3
Order By: Relevance
“…This situation is pushing policymakers to take actions to improve the quality of corporate disclosure. For example, pressures resulting from the UN's SDGs are provoking an increase in risk disclosure relating to the CSR risks, such as environmental, social, and sustainability issues [5]. The European Union also has further confirmed its commitment in the sustainable development [6] and the recent directive 2014/95/EU directing large companies to disclose several nonfinancial information that has been implemented in Italy by Legislative Decree No.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is pushing policymakers to take actions to improve the quality of corporate disclosure. For example, pressures resulting from the UN's SDGs are provoking an increase in risk disclosure relating to the CSR risks, such as environmental, social, and sustainability issues [5]. The European Union also has further confirmed its commitment in the sustainable development [6] and the recent directive 2014/95/EU directing large companies to disclose several nonfinancial information that has been implemented in Italy by Legislative Decree No.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sustainability reporting is generally conducted using the annual report media. Truant et al [34] reported that sustainability risk disclosure of a sample of large Italian organizations is positively influenced by the international presence and sustainability experience but it is not affected by the presence of external assurance. Dobre et al [35] found that environmental and social protection reported by Romanian listed companies could have an effect on the long-run financial performance.…”
Section: Sustainability Reportingmentioning
confidence: 99%
“…Other approaches to measurement include efficiency, in terms of value created per unit of environmental or social damage [35,36]. Several other measurement tools exist, such as qualitative sustainability initiatives, benchmarking standards, and survey-based approaches [37,38]. While each approach has its critics, researchers argue in favor of separating sustainability into its three dimensions for operational level decision-making.…”
Section: Measures Of Total Sustainabilitymentioning
confidence: 99%